(untitled) (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2017)
Abstract The Ministry of Religion in 2014 conducted a pilot implementation of the 2013 curriculum for the subjects of Islamic Education and Arabic. This study focuses on the policy of implementation and implementation of Curriculum 2013 in Madrasah Aliyah (MA) of West Java. This study uses quantitative approach. The research subjects were madrasah head, teacher, learner, supervisor, and madrasah committee. The instruments used were questionnaires, interview guides, and documentation. The data was analyzed using quantitative descriptive technique. The results show that most respondents understand the purpose of the implemented curriculum 2013 and the scientifc approach used. In the implementation of the 2013 curriculum, most of the respondents also stated that PAI teachers already have the ability to learn in the 2013 curriculum. The 2013 Curriculum Implementation also has a positive impact for students, teachers and Madrasah Aliyah. Nevertheless, there are still some problems that arise related to infrastructure, teacher training, teacher and student handbooks, and the absence of monitoring and evaluation monitoring from the government towards the implementation of Curriculum 2013. Â Abstrak Kementerian Agama pada tahun 2014 melakukan uji coba implementasi kurikulumm 2013 untuk mata pelajaran Pendidikan Agama Islam dan Bahasa Arab. Studi ini memfokuskan pada kebijakan implementasi dan penelahaan terhadap implementasi Kurikulum 2013 di Madrasah Aliyah (MA) wilayah Jawa Barat. Penelitian ini menggunakan pendekatan kuantitatif. Subjek penelitian adalah kepala madrasah, guru, peserta didik, pengawas, dan komite madrasah. Instrumen yang digunakan yaitu lembar angket, pedoman wawancara, dan dokumentasi. Analisis data menggunakan teknik deskriptif kuantitatif. Hasil penelitian menunjukkan bahwa sebagian besar responden memahami tujuan dari diimplementasikan kurikulum 2013 dan pendekatan saintifk yang digunakan. Dalam implementasi kurikulum 2013, sebagian besar responden juga menyatakan yakin bahwa para guru PAI sudah memiliki kemampuan dalam pembelajaran dengan kurikulum 2013. Implementasi Kurikulum 2013 juga memiliki dampak positif baik bagi peserta didik, guru, dan Kepala MA. Namun demikian masih ada beberapa permasalahan yang muncul terkait dengan sarana prasarana, pelatihan guru, buku pegangan untuk guru dan siswa, serta tidak adanya evaluasi dan monitoring monitoring dari pemerintah terhadap implemntasi Kurikulum 2013.